The role of segmental and suprasegmental features of English pronunciation”: “the case of Tercero de Bachillerato General Unificado “A” at Unidad Educativa Juan de Velasco, in the city of Riobamba, Chimborazo province during the academic period february 2021 – july 2021 - Villarreal Minga, Jhanela Patricia (2022)
The role of segmental and suprasegmental features of pronunciation are important in the teaching and learning process of the English language. In this sense, students will be able to develop their ability to speak and communicate effectively, clearly and fluently, since the learning of these characteristics allows them to understand and distinguish the different meanings that occur in the same sentence or word, thus preventing misunderstandings or misrepresentations. Through a previous study carried out in the Unidad Educativa Juan de Velasco, it has been determined as a problem that the teaching and practice of pronunciation has been neglected, therefore, this does not allow the development of the communicative ability of the students in the English language in the Tercero de Bachillerato General Unificado. This research focused on analyzing the role of segmental and suprasegmental features of English pronunciation. Therefore, the research applied a qualitative and descriptive approach. The techniques to collect data were interview, survey and observation which were applied with their corresponding instruments which are ethnographic interview, questionnaire and observation sheet. The population considered for the research were 30 students and an English teacher of the Tercero de Bachillerato General Unificado “A” at Unidad Educativa Juan de Velasco. The results of this research were described through a descriptive analysis of the importance and effectiveness of the teaching of pronunciation features in the linguistic development of the English language.